TAKING INTO ACCOUNT STOCHASTIC FACTORS IN THE GLOBAL ENVIRONMENTAL ECONOMIC MATHEMATICAL MODELS - Onyshkevych, Volodymyr; Gapalyak , Chrysnyna (Forestry, Forest, Paper and Woodworking Industry, 2011)
The necessity of analysis of environmental economic factors for modeling of global processes is motivated. On the basis of improvement of J. Forrester’s model, feasibility of taking into account stochastic factors during mathematical modeling of such processes is proposed.